2006
DOI: 10.1093/ndt/gfl570
|View full text |Cite
|
Sign up to set email alerts
|

Trisodium citrate 4%--an alternative to heparin capping of haemodialysis catheters

Abstract: Citrate 4% has equivalent or better outcomes with regards to catheter exchange, TPA use and access-related hospitalizations compared with heparin locking. It is a safe and less expensive alternative. Randomized trials comparing these anticoagulants with a control group would definitively determine the optimal haemodialysis catheter locking solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 28 publications
2
87
1
2
Order By: Relevance
“…The cost-effectiveness of rt-PA/heparin in comparison to other locking agents, such as citrate, 10 and in comparison to other prophylactic strategies, such as the use of topical polysporin triple, or mupuricin 19 is uncertain. How might renal programs use the results of this study?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-effectiveness of rt-PA/heparin in comparison to other locking agents, such as citrate, 10 and in comparison to other prophylactic strategies, such as the use of topical polysporin triple, or mupuricin 19 is uncertain. How might renal programs use the results of this study?…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Given these adverse outcomes and high costs, further research on strategies to optimize the use of hemodialysis catheters is required, particularly with regard to preventing the most common adverse catheter outcomes of malfunction (i.e., inability to initiate or continue dialysis because of to inadequate bloodflow, often the result of catheter thrombosis) and bacteremia. 5,6 Heparin has traditionally been used as an intradialytic catheter locking solution, although other agents are now used, including citrate 10,11 and recombinant tissue plasminogen activator (rt-PA). 12 Intradialytic locking with a thrombolytic agent has many appealing features.…”
mentioning
confidence: 99%
“…Two prospective observational studies conducted in Canada (40,41) showed either equivalence or a lower rate of TDC exchange and tPA use without a change in hospitalization for TSC 4% versus heparin. The largest experience reported is that from Grudzinski et al (42) during a conversion study from heparin 10,000 U/ml to 4% citrate locks.…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…Various concentrations of TSC have been used as catheter lock solutions. Lok et al investigated the clinical effectiveness, safety and cost of 4% citrate vs. heparin and found that 4% citrate lock solution had equivalent or better outcomes in terms of catheter exchange, thrombolytic use and access-related hospitalizations compared with the heparin lock solution (36). In our study, although not statistically significant, the development of thrombosis was lower in E-TSC group than heparin group (23.5% vs. 33.3%, respectively).…”
Section: Referencesmentioning
confidence: 42%